THE ANALYSIS OF TREND OF SWIMMING RESULTS IN MONTENEGRO FROM 2000-2009 - Branislav Radulović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
Following a ten years distribution of the best swimming results in Montenegro, an attempt to determine their dynamics was made, aimed to give a more detailed insight into the state of swimming sport. While the average values of all results remain for years on approximately the same level, their oscilations are evident inside the groups, primarily because of the small number of more quality swimmers. The population of women swimmers has achieved a much better results, compared to man swimmers, for the defined period. The high percentage of the registrated results was achieved by crawl technique in short distances, which indicates insufficient specialization in swimming disciplines. Also, almost all the best achievements for each analysed year come from two clubs, which among other things indicates the need for increase in quality swimming base, as one of the basic preconditions for the developement of the swimming sport.